Income, Service Convenience, and Consumptive Attitudes: Determinants of Shopee Paylater Adoption among Gen Z Consumers - Faiz Maynaldi Pratama; Rahmad Hakim; Rahmi Amalia; Ririn Noviyanti (Islamic Economics Journal, 2025)
The purpose of this research is to test and analyze whether income, convenience, and consumer behavior influence the decision to use Shopee Paylater. The research method used in this research is quantitative research with a descriptive design. The analysis method used in this research uses SEM-PLS (Structural Equation Modeling - Partial Least Structural). This research data was obtained from 103 respondents as research material. In processing the data, we used SmartPLS 4.0 software for Windows 11. The results of this research show that: first, income significantly influences the decision to use Shopee Paylater; second, convenience significantly influences the decision to use Shopee Paylater; and third, consumer behavior significantly influences the decision to use Shopee Paylater. The research implies that businesses can enhance adoption by addressing these factors and tailoring their products to meet the specific needs of younger consumers, while also opening avenues for future studies on trust, risk, and cross-cultural comparisons in digital finance adoption.